Anisotropic 1-Laplacian problems with unbounded weights - Ortiz Chata, Juan C. [UNESP]; Pimenta, Marcos T. O. [UNESP]; Segura de León, Sergio (Springer Nature, 2021)
In this work we prove the existence of nontrivial bounded variation solutions to quasilinear elliptic problems involving a weighted 1-Laplacian operator. A key feature of these problems is that weights are unbounded. One of our main tools is the well-known Caffarelli-Kohn-Nirenberg’s inequality, which is established in the framework of weighted spaces of functions of bounded variation (and that provides us the necessary embeddings between weighted spaces). Additional tools are suitable variants of the Mountain Pass Theorem as well as an extension of the pairing theory by Anzellotti to this new setting.
Keywords: 1-Laplacian operator; Caffarelli–Kohn–Nirenberg inequality; Weighted L∞–divergence–measure vector fields; Weighted quasilinear elliptic problems